The native sand sage vegetation of eastern Colorado - Daley, Richard Halbert, author; Dix, R. L., advisor; Cringan, A. T., committee member; Berg, William, committee member; Ward, R. T., committee member (Colorado State University. Libraries, 1972)
The native sand sage (Artemisia filifolia Torr.) vegetation in eastern Colorado has only received brief mention in the literature, and has never before been quantitatively studied. Consequently, this study was undertaken to provide a quantitative phytosociological description of the native sand sage vegetation. In addition, the vegetational-environmental complex was examined, and the relationship of this vegetation with other examples of sand vegetation in the North American grassland is suggested. This study is of timely importance because the land-use practices in eastern Colorado will likely destroy the last remnants of the native sand sage vegetation within a few years. Colorado's sand sage vegetation appears to be a climax edaphic variant of the mixed-grass prairie. Furthermore, based upon species composition differences between northeastern and southeastern Colorado stands, the possibility of a tension zone between the northern and the southern Plains through central Colorado is suggested. In addition to Artemisia filifolia, the most important species are Sporobolus cryptandrus, Bouteloua gracilis, and Helianthus petiolaris. Changes in species composition within each area are primarily a function of changes in slope and exposure. Significant differences in species importances between the northern and the southern stands are noted. Stipa comata and Calamovilfa longifolia, which are quite common in the northern stands, do not occur in quadrats in the south. These differences are accounted for by differences in substrate stability and climate. Substrate stability differences are hypothesized to account for the growth-form differences between the two Colorado study areas, which are similar, and the "stabilized dunes" of Saskatchewan and the sand sage vegetation of Nebraska, which are similar.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Botany -- Colorado; Botany; Colorado